The Role of Mother in Informing Girls About Puberty: A Meta-Analysis Study - Sooki; Shariati; Chaman; Khosravi; Effatpanah; Keramat (Kashan University of Medical Sciences, 2016)
Context Family, especially the mother, has the most important role in the education, transformation of information, and health behaviors of girls in order for them to have a healthy transition from the critical stage of puberty, but there are different views in this regard. Objectives Considering the various findings about the source of information about puberty, a meta-analysis study was conducted to investigate the extent of the mother's role in informing girls about puberty. Data Sources This meta-analysis study was based on English articles published from 2000 to February 2015 in the Scopus, PubMed, and Science direct databases and on Persian articles in the SID, Magiran, and Iran Medex databases with determined key words and their MeSH equivalent. Study Selection Quantitative cross-sectional articles were extracted by two independent researchers and finally 46 articles were selected based on inclusion criteria. STROBE list were used for evaluation of studies. Data Extraction The percent of mothers as the current and preferred source of gaining information about the process of puberty, menarche, and menstruation from the perspective of adolescent girls was extracted from the articles. The results of studies were analyzed using meta-analysis (random effects model) and the studies' heterogeneity was analyzed using the I2 calculation index. Variance between studies was analyzed using tau squared (Tau2) and review manager 5 software. Results The results showed that, from the perspective of teenage girls in Iran and other countries, in 56% of cases, the mother was the current source of information about the process of puberty, menarche, and menstruation. The preferred source of information about the process of puberty, menarche, and menstruation was the mother in all studies at 60% (Iran 57%, and other countries 66%). Conclusions According to the findings of this study, it is essential that health professionals and officials of the ministry of health train mothers about the time, trends, and factors affecting the start of puberty using a multi-dimensional approach that involves religious organizations, community groups, and peer groups.